2022
DOI: 10.1101/2022.02.25.482034
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widening the landscape of transcriptional regulation of green algal photoprotection

Abstract: Availability of light and CO2, substrates of microalgae photosynthesis, is frequently far from optimal. Microalgae activate photoprotection under strong light, to prevent oxidative damage, and the CO2 Concentrating Mechanism (CCM) under low CO2, to raise intracellular CO2 levels. Both processes are controlled by the nuclear factor CIA5/CCM1; yet, the underlying upstream transcriptional regulators remain largely unknown. By employing a large transcriptomics data compendium of Chlamydomonas reinhardtii’s respons… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 90 publications
(196 reference statements)
0
12
0
Order By: Relevance
“…LCR1 is instrumental in the activation of the CCM under CO 2 -limiting conditions, notably regulating the expression of CAH1 and LCI1 (Yoshioka et al, 2004). Conversely, under high-light conditions, LCR1 is critical for the expression of LHCSR3 , essential for photoprotection (Arend et al, 2023). However, our study revealed that LCR1 did not regulate LHCSR3 expression under CO 2 -limiting conditions (Table 1), demonstrating that the genes controlled by LCR1 vary with environmental context.…”
Section: Discussionmentioning
confidence: 99%
“…LCR1 is instrumental in the activation of the CCM under CO 2 -limiting conditions, notably regulating the expression of CAH1 and LCI1 (Yoshioka et al, 2004). Conversely, under high-light conditions, LCR1 is critical for the expression of LHCSR3 , essential for photoprotection (Arend et al, 2023). However, our study revealed that LCR1 did not regulate LHCSR3 expression under CO 2 -limiting conditions (Table 1), demonstrating that the genes controlled by LCR1 vary with environmental context.…”
Section: Discussionmentioning
confidence: 99%
“…Gene Ontology (GO) terms were transferred based on the best blastp (Altschul et al, 1990) hit from A. thaliana to the other species with a blastp (e < 1e-5) to exclude annotation artefacts introduced by different GO annotations. Genes with a weight greater than 0.005 were considered as target of the transcription factor (Arend et al, 2023; Halpape et al, 2023; Wulf et al, 2023). For each target list of the transcription factors a GO term enrichment was performed with topGO (v2.52.0) (Alexa and Rahnenführer, 2023) using the classic fisher method for the ontology biological process with a significance cut-off at p-value < 1e-10 (Table S5).…”
Section: Methodsmentioning
confidence: 99%
“…Network inference with the random forest decision tree-based algorithm GENIE3 (Huynh-Thu et al, 2010) was used to infer a gene regulatory network (GRN) in wheat (Ramírez-González et al, 2018) and analyze polyploid evolution (Almeida-Silva and Van de Peer, 2023). Recently, GENIE3 was used for identification and validation of regulators involved in photosynthesis in A. thaliana (Halpape et al, 2023) and in the regulation of photoprotection and the carbon concentrating mechanism in Chlamydomonas reinhardtii (Arend et al, 2023; Wulf et al, 2023) making it a promising candidate to compare gene regulatory networks across species. By performing GRN inference based on expression data comparability of individual samples is not necessary, because transcription factors are examined in relation to all other genes.…”
Section: Introductionmentioning
confidence: 99%
“…Several large to very large expression datasets pertaining to the induction of PP have been produced in C. reinhardtii, such as a diurnal dataset (Zones et al, 2015), CO2 concentration changes (Fang et al, 2012), and redox challenges (Ma et al, 2020). A curated set of expression data was successfully used to identify QER7, which controls the expression of PP genes (Arend et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Limiting CO2 supply rapidly activates the response factor LCRF and this TF triggers the accumulation of the nucleic acid binding protein NAB1, which in turn enhances the translational repression of PSII-associated light-harvesting proteins (LHCBMs) (Blifernez-Klassen et al, 2021). The CO2 inputs are transduced via the transcriptional regulator CIA5 (also named CCM1) to both CCM and PP gene expression (Fang et al, 2012) and via the myb-type TF LCR1 (for low-CO2 stress response) (Yoshioka et al, 2004; Arend et al, 2023). The TF qE-REGULATOR 7 (QER7) belonging to the SQUAMOSA-PROMOTER BINDING PROTEIN-LIKE gene family was identified via network analyses also controls both PP and CCM genes (Arend et al, 2023).…”
Section: Introductionmentioning
confidence: 99%